Subtleties in Concluding and Executing Contracts in E-Commerce in the Republic of Uzbekistan - Sitora Mengliyeva Baxtiyor kizi; Bekhzod Khudayberganov Bakhtiyorivich (Research Parks Publishers, 2023)
This article is devoted to the study of the difficulties associated with the conclusion and execution of contracts in the field of e-commerce. The article considers the main aspects for concluding contracts in e-commerce, including performance and validity conditions. In addition, she examines the legal framework governing the conclusion of contracts and the possibility of using electronic contracts. In addition, the article discusses the importance of the procedures for concluding contracts in the context of electronic interaction. The purpose of this article is to provide a comprehensive understanding of the important points associated with the conclusion and execution of contracts in e-commerce.